Pengembangan E-Modul Berbasis Socio Scientific Issues (SSI) pada Materi Laju Reaksi untuk Meningkatkan Keterampilan Berpikir Kritis - Yuli Rahmayani Hasibuan; Gulmah Sugiharti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to develop a Socio-Scientific Issues (SSI)-based chemistry learning e-module on reaction rates to improve students' critical thinking skills. This research is based on students' low critical thinking skills due to the lack of interactive and contextual teaching materials. The study was conducted at SMA Negeri 1 Batang Kuis using the ADDIE development model. The developed e-module includes various learning components designed based on SSI syntax and packaged interactively through the Flip Corporate Edition platform. Validation results from material and media experts indicate that the e-module is categorized as feasible, with an average score of 3.49 (very valid) for lecturers and 3.67 (very valid) for teachers. The media feasibility test was categorized as feasible with an average score of 3.95 (very valid). Meanwhile, the percentage of student responses in using the e-module was 95.75%. These results indicate that the developed e-module can be used as an alternative teaching material to support chemistry learning and improve students' critical thinking skills.